Pseudomonas aeruginosa encapsulated with calcium carbonate microshells for potential biocontrol of the Ganoderma boninense - Mustafa, Isshadiba Faikah; Hussein, Mohd Zobir; Idris, Abu Seman; Ramli, Nur Rashyeda; Mustafa, Muskhazli; Fakurazi, Sharida (Springer, 2023)
The endophytic bacterium, Pseudomonas aeruginosa, was successfully encapsulated into calcium carbonate microshells and coated with sodium alginate in combination with two other materials: skim milk and empty fruit bunch (EFB). The presence of bacteria cells was confirmed by a strand-like structure, a biofilm through morphology and elemental analysis. The survivability of microencapsulated bacteria was found to last for 17 months when they were maintained in a storage condition of 4 °C. Different coating materials used exhibited significant differences in the P. aeruginosa survival during the storage time. Their bioactivity against Ganoderma boninense resulted in a percentage inhibition radial growth (PIRG) value of more than 70%, which is better than its counterparts, the free Pseudomonas cells. With promising viability results of × 106 CFU/mL after three-month storage, the results demonstrate that skim milk-coated alginate might be good protection for P. aeruginosa that could sustain the viable bacteria at the target site. This is toward a greener, biological control-based plant protection for Ganoderma diseases in the oil palm planting industry.